Faktor-Faktor yang Berhubungan dengan Tingkat Kecemasan Pasien Kanker Payudara dengan Kemoterapi - Marsaid Marsaid; Sisca Nofiyanti Setya Rahayu; Abdul Hanan; Ira Rahmawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Anxiety is the most common problem experienced by breast cancer patients with chemotherapy. The purpose of this study was to determine the factors associated with the level of anxiety in breast cancer patients with chemotherapy. This study uses a literature review method using the keywords: Anxiety, Breast Cancer, Chemotherapy. The articles are taken from several databases, namely PubMed, Willey, Google Schoolar, ScienceDirect and Research Gate secondary sources in the 2015-2020 range. The selection was taken using JBI Critical Appraisal Tools and paying attention to the PEOS framework, then the articles were analyzed one by one. There were 212 articles, selected and 10 articles that met the inclusion and exclusion criteria. The results of the review of the 10 articles showed factors related to the level of anxiety in breast cancer patients with chemotherapy, 5 articles indicated the age factor, 4 articles indicated the education level factor, 3 articles indicated the coping strategy factor, 2 articles indicated the residence factor, the cancer stage, social support factors, and information access factors, as well as 1 article showing the optimism factor, the physical integrity threat factor, and the self-system threat factor. A total of 6 articles showed that patients with breast cancer undergoing chemotherapy experienced moderate anxiety. The dominant internal factor is age, while the external factor is social support. Although the anxiety experienced by the majority of respondents is moderate, if the factors causing the increase in anxiety levels are not known, it can hinder the treatment process for patients with breast cancer.Keywords: anxiety; breast cancer; chemotherapy ABSTRAK Kecemasan merupakan masalah yang paling sering dialami pasien kanker payudara dengan kemoterapi. Tujuan dari studi ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan tingkat kecemasan pada pasien kanker payudara dengan kemoterapi. Studi ini menggunakan metode literature review dengan menggunakan keywords: Anxiety, Breast Cancer, Chemotherapy. Artikel diambil dari beberapa database yaitu PubMed, Willey, Google Schoolar, ScienceDirect dan sumber sekunder Research Gate pada rentang tahun 2015-2020. Penyeleksian diambil dengan menggunakan JBI Critical Appraisal Tools dan memerhatikan PEOS framework, kemudian artikel dianalisis satu persatu. Ditemukan sebanyak 212 artikel, diseleksi dan yang memenuhi kriteria inklusi dan ekslusi adalah 10 artikel. Hasil review dari 10 artikel tersebut menunjukkan faktor-faktor yang berhubungan dengan tingkat kecemasan pada pasien kanker payudara dengan kemoterapi, 5 artikel menunjukkan faktor usia, 4 artikel menunjukkan faktor tingkat pendidikan, 3 artikel menunjukkan faktor strategi koping, 2 artikel menunjukkan faktor tempat tinggal, faktor stadium kanker, faktor dukungan sosial, dan faktor akses informasi, serta 1 artikel menunjukkan faktor optimisme, faktor ancaman integritas fisik, dan faktor ancaman sistem diri. Sejumlah 6 artikel menunjukkan pasien dengan kanker payudara yang menjalani kemoterapi mengalami kecemasan sedang. Faktor internal yang dominan yaitu usia, sedangkan faktor eksternal yaitu dukungan sosial. Meskipun kecemasan yang dialami mayoritas responden sedang, namun apabila tidak diketahui faktor penyebab bertambahnya tingkat kecemasan dapat menghambat proses pengobatan pasien dengan kanker payudara.Kata kunci: kecemasan; kanker payudara; kemoterapi